Austin Powers : Goldmember # 3 - Copyright Collection (Library of Congress) ([Place of publication not identified] : [Publisher not identified], 2002)
Plot Synopsis by Michael Hastings Mike Myers' phenomenally successful spy spoof gains a few more characters, a slew of celebrity cameos, and even more free-associative laughs in this third installment of the popular franchise. Austin Powers in Goldmember continues the exploits of the swinging-'60s leftover, who, as the film opens, is busy critiquing a big-budget Hollywood production of his life story, replete with a 20-million-dollar star in the lead role and a slew of John Woo-style action scenes. But not far from the soundstage lurks arch nemesis Dr. Evil (Myers), who has opened up a talent agency representing some of the industry's biggest stars all the while channeling their profits into a diabolical world-destruction plan with the unfortunate code name Preparation H. Dr. Evil presents a distraction to Austin by kidnapping his similarly swingin' father, Nigel Powers, and transporting him back in time to 1975. Travelling there to save his father and in turn win back his dad's sometimes-errant affection Austin comes across the alluring superspy Foxxy Cleopatra (Beyonce Knowles). The three of them travel back to the present day, where they join forces to battle Dr. Evil and his posse of nefarious evil-doers, including the trusty clone Mini-Me (Verne Troyer); his snotty son, Scott (Seth Green); the inimitable Fat Bastard (Myers); and the eponymous new addition to the fold: the epidermis-obsessed, precious-metal-fortified Dutchman called Goldmember (Myers).
Copyright: New Line Productions, Inc. Appl. au.: Avery Pix, Inc., employer for hire. Prev. reg.: Original screenplay prev. reg. NM: all other cinematographic materials. DCR 2002; PUB 26Jul02; REG 21Aug02; PA1-097-809.
Sources used: copyright data base; copyright data sheet.
Austin Powers.
interactive DVD-ROM
Keywords: Comedy -- Feature